Chromosome fragility in Freemartin cattle - V. Barbieri; L. Iannuzzi; G. P. Di Meo; G. Beneduce; R. Buonerba; S. Albarella; V. Peretti; F. Ciotola (Italian Journal of Animal Science, 2010)
The aim of the present study was to verify chromosome fragility in freemartin cattle using chromosome aberration (CA) and sister chromatid exchange (SCE) tests. A total of eighteen co-twins were investigated. Fourteen animals were identified as cytogenetically chimeric (2n=60, XX/XY) while 4 were classified as normal. Freemartin cattle showed a higher percentage of aneuploid cells (18.64%) and highly significant statistical differences (P < 0.001) in mean values of gaps (4.53 ± 2.05), chromatid breaks (0.26 ± 0.51), and significant statistical differences (P < 0.005) in mean values of chromosome breaks (0.12 ± 0.43) when compared to 10 control animals from single births (aneuploid cells, 11.20%; gaps, 2.01 ± 1.42; chromatid breaks, 0.05 ± 0.22; chromosome breaks, 0.02 ± 0.14).